Comparison of Viral Clearance between Ivermectin with Doxycycline and Hydroxychloroquine with Azithromycin in COVID-19 Patients - Rahman, Md Azizur; Iqbal, Syed Asif; Islam, Md Azizul; Niaz, Md Kaisar; Hussain, Tahmeed; Siddiquee, Taufiqul Hasan (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: The whole world is on the brink of collapse due to the outbreak of COVID-19 with no solution to treat these cases with any specific drug. Extensive search for the Vaccine or effective treatment is going on while alarming infection and death toll is rising every day. Aim: The study will compare the effect of Ivermectin with Doxycycline and Hydoxychloroquine with Azythromicin on a selective group of COVID -19 positive patients. Method: This is a comparative study that included 400 patients of COVID 19 positive patient who were divided in to two groups. Group- A Received Ivermectin with Doxycycline and the other group- B received hydroxichloroquine(HCQ) with azithromycin. Result: Viral clearance is 132 ( 66%) on day 5 and 167( 83.5% ) on day 6. Among them 33(16.5%) remain PCR positive after 6th day of Ivermectin ingestion in Group A. Whereas there is154 ( 77.0%) viral clearance at 11th day and 163(81.5%) viral clearance at 12th day of Hydroxychloroquine ingestion in Group B. Among them 37 (18.5%) remain PCR positive after 12 day in group B. The P value is 0.000427 which is significant considering 5th day viral clearance of Ivermectin ingestion and 11th day of Hydroxychloroquine ingestion. But considering 6th day and 12th day the P-value is 0.59 which is not significant. Conclusion: It appears Ivermectin and Doxycycline is safeand effective combination drug therapy in COVID- 19infected patients but need further extensive study to find out the scope of application on other groups of patients. J Bangladesh Coll Phys Surg 2020; 38(0): 5-9